Prevalence of clinical signs and symptoms of the masticatory system and their associations in children with sleep bruxism: A systematic review and meta-analysis. (June 2021) - Soares, Josiane Pezzini; Moro, Juliana; Massignan, Carla; Cardoso, Mariane; Serra-Negra, Júnia Maria; Maia, Lucianne Cople; Bolan, Michele
Summary: Sleep bruxism (SB) is a behavior of central origin that is related to different factors. This systematic review aimed to determine the prevalence of clinical signs and symptoms of the masticatory system and their association in children with SB. A structured search in ten databases were taken. Two authors independently selected studies, extracted the data, study quality assessment and graded the evidence. A meta-analysis of proportion and association was performed under random-effect model, confidence interval of 95% and p < 0.05 for pulled values. Were included 22 studies, and their overall quality was poor. The more common clinical signs and symptoms of the masticatory system in children with SB were primary canine wear (P:84.13, 95% CI:78.13–89.32; p = 0.248; I 2 25.05), dental wear (P:73.76, 95% CI:38.73–96.91; p < 0.001; I 2 97.62) and headache (P:52.85, 95% CI:38.92–66.56; p < 0.001; I 2 93.65). The prevalence of SB in children was 31.16% (P:31.16, 95% CI:22.18–40.92; p < 0.001; I 2 98.56). There was no significant risk of dental wear and headache in children with SB. There is low to very low certainty of the evidence. The more prevalent clinical signs and symptoms of the masticatory system presented in children with SB were primary canine wear, dental wear and headache. Further studies of high quality are still needed to elucidate these important questions.